2010
DOI: 10.1016/j.vaccine.2010.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal administration of RiVax protects mice from mucosal and systemic ricin intoxication

Abstract: Ricin toxin is a CDC level B biothreat. We have developed a ricin vaccine, RiVax, which is a recombinant mutant of ricin A chain. RiVax is safe, immunogenic and protective in mice when administered intramuscularly (IM). We have now attempted to increase the utility and immunogenicity of RiVax by administering it intradermally (ID) with or without alum. Without alum, Rivax administered by the ID and IM routes was equally immunogenic and protective. With alum, ID vaccinations were more immunogenic and protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…), subcutaneous (s.c.), or intradermal (i.d.) route elicits toxin-specific serum IgG antibodies (Abs) that are sufficient to confer protection against a lethal dose of ricin (8)(9)(10)(15)(16)(17). Phase I clinical trials have demonstrated that RiVax is safe and immunogenic in healthy human volunteers (18,19).…”
mentioning
confidence: 99%
“…), subcutaneous (s.c.), or intradermal (i.d.) route elicits toxin-specific serum IgG antibodies (Abs) that are sufficient to confer protection against a lethal dose of ricin (8)(9)(10)(15)(16)(17). Phase I clinical trials have demonstrated that RiVax is safe and immunogenic in healthy human volunteers (18,19).…”
mentioning
confidence: 99%
“…or intradermally (i.d.) with three doses of as little as 1 g each were uniformly protected from a subsequent ricin challenge (10 50% lethal doses [LD 50 s]) administered by injection, aerosol, or intragastric gavage (10,15,16).…”
mentioning
confidence: 99%
“…However, while such results were encouraging, vaccine formulation and stability remain problematic. Hence, a lyophilized formulation that retained immunogenicity when stored at 4ºC was developed (Smallshaw & Vitetta, 2010;Marconescu et al, 2010).…”
Section: Vaccination and Passive Protectionmentioning
confidence: 99%